Revision of the Taiwanese species of the genus Leptophion Cameron, 1901 (Hymenoptera: Ichneumonidae: Ophioninae), with a discussion of their phenology and distribution - Shimizu, So; Watanabe, Kyohei; Maeto, Kaoru (Zootaxa, 2016)
We revise the Taiwanese species of the ophionine genus Leptophion Cameron, 1901. As a result, three species, including a new species, are recognized. Two of them were identified as L. maculipennis (Cameron, 1905) and L. radiatus (Uchida, 1956), both of which had been previously recorded in Taiwan; we redescribe them based on Taiwanese specimens. We describe a single new species as L. giganteus Shimizu & Watanabe, sp. nov. The phenology and distribution of the species are briefly discussed. A key to the Taiwanese species of Leptophion and additional couplets to the key proposed by Gauld & Mitchell (1981) are also provided.